Studies on microstructural and mechanical properties of (Nano SiC + Waste Spent catalyst) reinforced aluminum matrix composites. (March 2022) - Pragathi, P.; Elansezhian, R.
Abstract: In the concept of reuse and recycling, the waste alumina spent catalyst from the oil refineries is used as a reinforcement in aluminum composites. For this purpose, aluminum composites with the addition of nano SiC/Spent catalyst were fabricated using the stir casting process. The composites were prepared by reinforcing pure aluminum with 10 wt%spent catalyst and varying the nano SiC by 0.5, 1, 1.5, and 2 wt% respectively. The mechanical and microstructural properties of produced composites were then examined. The microstructure reveals that the nano SiC and spent catalyst were distributed uniformly in the pure aluminum matrix. The mechanical properties of fabricated composites were compared to pure aluminum. The fabricated aluminum compositesAl + 10 wt% Spent Catalyst + 1.5 wt% nano SiC demonstrates a maximum increase in hardness 99.80 HRB, tensile and compressive strength UTS = 134.53 MPa, UCS = 226 MPa compared to pure aluminum. As a result, the addition of different percentages of nano SiC / Spent catalyst to pure aluminum results in higher mechanical strength compared to the composite without reinforcement. Graphical Abstract: ga1 Highlights: Aluminum composites with the reinforcement nano SiC and spent catalyst were fabricated using the stir casting technique. The reinforcement nano SiC and spent catalyst showed a major impact on the mechanical properties of pure aluminum. Addition of nano SiC and spent catalyst reinforcement increased the hardness, tensile and compressive strength of composites.